Codependency in nurses and related factors (Annals of Medical Research, 2021)
Aim: The study that aims to examine codependence in nurses and the factors that affect codependence has been planned in accordance with the descriptive research method. Material and Methods: The sample group of the study is comprised of 538 nurses that work at five state hospitals and one university hospital located inside the Gaziantep city limits who accepted to participate. Study data were acquired using an Individual Information Form with questions on socio-demographic characteristics and factors which are thought to have an impact on codependence, Nurse Codependency Questionnaire and Rosenberg Self-Esteem Scale. Data acquisition tools were applied during the dates of March 3 Mart – August 29, 2014.Result: The scores of nurses from Nurse Codependency Questionnaire was determined as 70.65±11.09, codependent caretaking subscale score average was determined as 40.03±8.31, lack of expression sub-scale score average was determined as 30.00±4.91 and Rosenberg self-esteem scale score average was determined as 22.67±4.15.Conclusions: It was determined that self-esteem, physical, emotional and sexual abuse during the pre-18 year old childhood period, physical and psychological problems, education level, working conditions and whether working hours are regular or not are all related with codependency in nurses. Keywords: Codependency; nurse; influencing factors.
Keywords: Codependency; nurse; influencing factors.